Training to Develop Science Process Skills of Students of SMA 6 Padang Pelawi, Seluma Regency Through Physics Ethnoscience Learning - Hamdani, Dedy; Putri, Desy Hanisa; Utama, Tiara Hardyanti; Ahda, Netriani Veminsyah; Wijaya, M. Abdilah Hananta; Cahyani , Dian Eka (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service project focuses on enhancing students' Science Process Skills (SPS) through the implementation of ethnoscience-based physics learning. The activity was conducted on August 1, 2024, at SMA Negeri 6 Padang Pelawi, Seluma Regency. The method of implementation included presentations, discussions, and hands-on practice with students. After applying the ethnoscience-based learning concept, there was a noticeable improvement in students' science process skills, both in observation and experimentation. Additionally, the effectiveness of the Discovery Learning and Problem-Based Learning (PBL) models was evident in improving students' science process skills through collaboration and problem-solving. Ethnoscience-based learning not only enhanced science process skills but also deepened students' appreciation of local culture. Through ethnoscience learning training at SMA Negeri 6 Padang Pelawi, Seluma Regency, it is hoped that the learning process can leverage local cultural diversity. This approach not only develops students' scientific skills but also strengthens the connection between physics concepts and local wisdom. This culturally-based learning provides relevant context, deepens students' understanding, and makes the learning process more meaningful.